Quasi-reversible energy flows in carbon-nanotube oscillators - Chwang, Allen T. (2012)
Quasi-reversible energy flows between orderly intertube axial motion and vibrational modes are studied for isolated systems of two coaxial carbon nanotubes at temperatures ranging from 300 K to 500 K. It is found that the excess intertube van der Waals energy, depleted from the intertube axial motion, is primarily stored in low-frequency mechanical modes of the oscillator for an extended period of time.